Engineering the Bacterial Microcompartment Domain for Molecular Scaffolding Applications - Young, Eric J.; Burton, Rodney; Mahalik, Jyoti P.; Sumpter, Bobby G.; Fuentes-Cabrera, Miguel; Kerfeld, Cheryl A.; Ducat, Daniel C. (Frontiers in Microbiology, 2017)
As synthetic biology advances the intricacy of engineered biological systems, the importance of spatial organization within the cellular environment must not be marginalized. Increasingly, biological engineers are investigating means to control spatial organization within the cell, mimicking strategies used by natural pathways to increase flux and reduce cross-talk. A modular platform for constructing a diverse set of defined, programmable architectures would greatly assist in improving yields from introduced metabolic pathways and increasing insulation of other heterologous systems. Here, we review recent research on the shell proteins of bacterial microcompartments and discuss their potential application as “building blocks” for a range of customized intracellular scaffolds. We summarize the state of knowledge on the self-assembly of BMC shell proteins and discuss future avenues of research that will be important to realize the potential of BMC shell proteins as predictively assembling and programmable biological materials for bioengineering.